Local health department effectiveness in addressing the core functions of public health - Turnock, B J; Handler, A; Hall, W; Potsic, S; Nalluri, R; Vaughn, E H (Public health reports (1974), 1994)
Objective 8.14 of the Year 2000 National Health Objectives calls for 90 percent of the population to be served by a local health department effectively carrying out the three core functions of public health--assessment, policy development, and assurance. To provide a benchmark of local health department effectiveness in addressing the core functions and to assess implications for achieving the year 2000 target, a random national sample (stratified by jurisdiction and population base) of local health departments was surveyed to determine self-reported compliance with 10 public health practice performance measures that operationalize the core functions. Overall compliance with the 10 performance measures was 50 percent, based on weighted responses of 208 responding health departments. Compliance was highest for the practices related to the assurance function and least for practices related to the policy development function. Compliance was also high for departments serving a population of 50,000 or more and those smaller departments organized at the city and city-county levels. Using two different definitions developed by the investigators, 19 and 31 percent of the health departments were judged to be effective in addressing the core functions of public health. These data suggest that less than 40 percent of the U.S. population was served by a health department effectively addressing the core functions of public health in 1993. It appears that considerable capacity building within the public health system will be needed to achieve the year 2000 target of 90 percent.